Application of green technologies in architecture - Sirija, M (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> The modern day construction activities use forms of energy and the natural resources on a large scale with the production of huge quantities of by-products. The production of tones of by- products is introducing unwanted materials into the environment as a result, further polluting it. The present day world is experiencing a number of problems like the different kinds of pollution (air, water, land and noise pollution), shortage of the natural resources etc. All this highlights the very need of protecting the environment and preserving it for the future generations, points towards the high need of adopting a sustainable way of construction and architecture.The purpose of this research is to highlight the raising need of adoption of green technologies especially in the field of architecture and construction for ensuring sustainable development in the present era. This paper specifies the definition of green architecture and covers the need, aspects, methods and its advantages, along with the use of various green technologies. It brings to fore the importance of green architecture for development in a sustainable way. It highlights the various green technologies by which sustainability in architecture can be achieved and adopted with its benefits to the environment as well as the society. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->